2014
DOI: 10.1016/j.jdent.2014.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Non-thermal atmospheric plasmas in dental restoration: Improved resin adhesive penetration

Abstract: Objective To investigate the influence of non-thermal plasma treatment on the penetration of a model dental adhesive into the demineralized dentin. Methods Prepared dentin surfaces were conditioned with Scotchbond Universal etchant for 15 s and sectioned equally perpendicular to the etched surfaces. The separated halves were randomly selected for treatment with an argon plasma brush (input current 6 mA, treatment time 30 s) or gentle argon air blowing (treatment time 30 s, as control). The plasma-treated spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 35 publications
2
46
2
1
Order By: Relevance
“…However, the cohesive failure modes also increased after aging, corroborating the findings of the present study for the direct water exposure storage protocol. Previous studies have reported that NTAP treatment of dentin before application of etch‐and‐rinse adhesive increased the μ TBS , supporting the findings of the present investigation for the simulated pulpal pressure‐aging protocol.…”
Section: Discussionsupporting
confidence: 91%
“…However, the cohesive failure modes also increased after aging, corroborating the findings of the present study for the direct water exposure storage protocol. Previous studies have reported that NTAP treatment of dentin before application of etch‐and‐rinse adhesive increased the μ TBS , supporting the findings of the present investigation for the simulated pulpal pressure‐aging protocol.…”
Section: Discussionsupporting
confidence: 91%
“…Scanning electron microscope images (Fig. 4c, d) also showed that resin tags were longer and more tortuous with lateral projections (Han et al 2014;Zhang et al 2014), reflecting an enhanced penetration of resin into dentin tubules and tubule branches thanks to more hydrophilic tubule walls as a result of NTAP treatment. The results were consistent with the notion (mentioned in the Dental Surface Modification section) that NTAP could increase the hydrophilicity/wettability of dentin collagen or substrates, which caused the preferential infiltration of hydrophilic components.…”
Section: Resin Penetrationmentioning
confidence: 92%
“…Their results indicated that cold plasmas were effective in deactivating oral bacteria in culture after 5 min of application, this might play some roles in prevention or treatment of dental caries. It was also found that the cold plasma treatment improved primer infiltration compared to a control 12) . One study revealed that atmospheric-pressure plasmas increased the surface energy and surface wettability of enamel, and as a result its bond strength with sealants, potentially serving as a substitute for conventional acid etching procedures or as an adjunct to self-etch sealants 13) .…”
Section: Introductionmentioning
confidence: 90%